Why and how to subsidise energy R+D: Lessons from the collapse and recovery of electricity innovation in the UK - Jamasb, Tooraj; Pollitt, Michael G. (Energy policy, 2015)
The UK electricity sector liberalisation was a pioneer in the worldwide reform trend and its reform model and outcomes have been the subject of many studies. However, lesser known are the effects of privatisation, market based reforms, and incentive regulation of networks on research and development as well as patenting activities in the sector. This paper updates our previous studies of this subject and discusses the recent developments in the innovative activities in the UK electricity sector. We find that, in recent years, the initial absence of support policies and the subsequent decline in innovation efforts in the aftermath of the reform has resulted in efforts towards forming an energy technology and innovation policy. Although we already observe some positive outcomes from these efforts, we discuss whether the balance of the innovation efforts are calibrated appropriately and whether the institutional framework can be further improved to promote long term progress. •We discuss the impact of electricity market reforms on innovation in the UK.•We show that both R+D expenditure and innovation output have recovered sharply.•We discuss some of the new institutional arrangements which have support this.•We conclude that new ways of supporting R+D are needed.